A multidisciplinary approach reveals a new species of glassfrog from Colombia (Anura: Centrolenidae: Nymphargus) - Montilla, Sebastián O.; Arcila-Pérez, Luisa F.; Toro-Gómez, María Paula; Vargas-Salinas, Fernando; Rada, Marco (Zootaxa, 2023)
Anurans of the family Centrolenidae are a highly diverse clade of Neotropical treefrogs. In the last two decades, glassfrogs have become a model system for studies in ecology and evolutionary biology, in part because their taxonomy and phylogenetic relationships are considered relatively well established. However, there are still many gaps in our knowledge, for example, which morphological characters are important for species delimitation. Consequently, several species complexes in Centrolenidae remain unresolved. Using data on external and internal morphology of adult individuals, tadpoles, advertisement call traits and genetic sequences, we describe a new species of glassfrog (Nymphargus pijao sp. nov.) endemic to Colombia that has been previously missasigned to Nymphargus griffithsi. We include in this description data of three phenotypic characters related to pectoral musculature and testis size, which have been traditionally overlooked in studies about the taxonomy and systematics of glassfrogs. In addition, we present details of a low-cost method implemented in the field to rear tadpoles of the new species. This methodology can solve common problems during the management and care of glassfrogs egg masses and tadpoles, and hence, promotes their description for more species and a better knowledge of the anuran biodiversity in Neotropics.